PENGARUH KEPALA SEKOLAH BUDAYA KINERJA GURU TERHADAP EFEKTIVITAS SEKOLAH - Nurhafifah Nurhafifah; Sulton Djasmi; Alben Ambarita (9 772338317006)
The purpose of this study was to determine and analyze the significant influence of school leadership, school culture and teacher performance on the effectiveness school of SMA Negeri District Pringsewu. This research is quantitative descriptive, population in this study is the number of teachers in SMA Negeri in District Pringsewu consisting of 9 State schools, This research is quantitative approach, by taking a sample of 89 teachers. Analysis of data using path analysis (path analysis). The results of this study indicate that principle leadership have a significant effect on the effectiveness school, school culture significantly influence the effectiveness school, and teacher performance significantly influence the effectiveness school. School leadership, school culture and teacher performance together have a significant effect on the effectiveness school. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis pengaruh signifikan kepemimpinan kepala sekolah, budaya sekolah dan kinerja guru terhadap efektivitas sekolah di SMA Kabupaten Pringsewu. Jenis penelitan ini adalah pendekatan kuantitatif, dengan mengambil sampel 98 guru. Pengumpulan data dilakukan dengan kuesioner. Analisi data menggunakan analisis jalur (path analysis). Hasil penelitian ini menunjukkan bahwa kepemimpinan kepala sekolah berpengaruh signifikan terhadap efektivitas sekolah, budaya sekolah berpengaruh signifikan terhadap efektivitas sekolah. Kinerja guru berpengaruh signifikan terhadap efektivitas sekolah. Kepemimpinan kepala sekolah, budaya sekolah dan kinerja guru secara bersama-sama berpengaruh signifikan terhadap efektivitas sekolah. Kata kunci: budaya sekolah, efektivitas sekolah, kepemimpinan, kinerja guru